Security Implications and Considerations for Femtocells - Chen, Jing; Wong, Marcus (Journal of Cyber Security and Mobility, 2012)
A Femto system is able to provide new services with higher data rate at relatively lower cost than traditional cellular system. Operators have already indicated their interest in this area and the number of deployments is ever increasing. Security is a critical part of Femto in all aspects of the operation of Femto services. In this paper, we analyze the security of Femto based on 3GPP system architecture. In addition, we will look into the details of other security aspects of Femto system, including security requirement and security mechanism.